Block shot eaudiobook - Ryan, Kennedy (Hoops, 2019)
JARED If I had a dollar for every time Banner Morales made my heart skip a beat . . . The heart everyone assumes is frozen over. Her anger is . . . arousing. Every glare from those fire-spitting eyes, every time she grits her teeth, gets me . . . well, you know. If I had a dollar for every time she's put me in my place, I'd be an even richer man. I'm a successful sports agent because I assume "no" means you'll think about it. I'm sure what you meant to say is, "Coming right up." They say even rich men don't always get what they want, but those men don't know how to play the game. The trick is to keep them guessing. Take Banner. She assumes she's winning, but this game? She doesn't even know how to play. BANNER If I had a dollar for every time Jared Foster broke my heart, I'd have exactly one dollar. One night. One epic fail. One dollar . . . and I'm out. I've moved on. I've found success in a field ruled by men. Anything they can do, I have done better. They can keep the field while I call the shots, blocking them when I have to. And Jared has the nerve to think he gets a second chance? Boy, please. Go sit down. Have several seats. I'll just be over here ignoring the man carved from my fantasies with a lust-tipped chisel. Oh, I didn't say the struggle wasn't real. But I've got that one dollar, and Jared won't have me. Contains mature themes.